INTEGRASI TEKNOLOGI DIGITAL DAN AI DALAM MEMPERKUAT AKUNTABILITAS PADA OPERASI MANAJEMEN RANTAI PASOKAN: ANALISIS LITERATUR SISTEMATIS - Eryc Eryc; Indasari Deu (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2024)
Digitalization and artificial intelligence (AI) have significantly transformed various aspects of business management, particularly in supply chain management. These technologies hold great potential to revolutionize supply chain optimization by enhancing transparency, enabling real-time monitoring, and improving decision-making accuracy. Additionally, digitalization and AI strengthen collaboration and communication among stakeholders while enhancing planning and forecasting, thereby supporting operational sustainability. Through bibliometric analysis and a systematic literature review using SCOPUS and Google Scholar databases, this study maps publication trends and explores the relationship between digitalization, AI, and accountability in supply chain management. The findings indicate that digitalization and AI not only contribute to operational efficiency but also enhance accountability and sustainability within supply chains. This study highlights the existing research gaps regarding the application of digitalization and AI in sustainability and provides recommendations for future research to develop a more comprehensive framework for measuring the impact of these technologies.